Imaging Water Thin Films in Ambient Conditions Using Atomic Force Microscopy - Santos, Sergio (Materials (Basel), 2016)
All surfaces exposed to ambient conditions are covered by a thin film of water. Other than at high humidity conditions, i.e., relative humidity higher than 80%, those water films have nanoscale thickness. Nevertheless, even the thinnest film can profoundly affect the physical and chemical properties of the substrate. Information on the structure of these water films can be obtained from spectroscopic techniques based on photons, but these usually have poor lateral resolution. When information with nanometer resolution in the three dimensions is needed, for example for surfaces showing heterogeneity in water affinity at the nanoscale, Atomic Force Microscopy (AFM) is the preferred tool since it can provide such resolution while being operated in ambient conditions. A complication in the interpretation of the data arises when using AFM, however, since, in most cases, direct interaction between a solid probe and a solid surface occurs. This induces strong perturbations of the liquid by the probe that should be controlled or avoided. The aim of this review is to provide an overview of different AFM methods developed to overcome this problem, measuring different interactions between the AFM probe and the water films, and to discuss the type of information about the water film that can be obtained from these interactions.